Se planta e colhe alimentos neste sertão : resistência e permanência da autonomia camponesa e as estratégias do MPA (Movimento dos Pequenos Agricultores) nas contradições do projeto da soberania alimentar - Santos, Ricardo Menezes (2012)
This dissertation has the objective of analyze the production unit of the rural family, from the Small Agriculture Movement MPA. To reach this objective, a historic study of the MPA was carried out, its organization, specialization, its relation with the rural way. We focused our research in the territory of the High back-country of Sergipe, which configures as a historic territory of permanence struggle of the rural production unit and its link with the MPA in the construction of the Feeding Sovereignty project. The option of the dialectic historic materialism method made possible the analysis of the historic process, realizing that, when making history in specific conditions, men start being determined and determiners from/by the nature and other men. Men, as historic individuals, appear not as fragments, but articulated in the group of structures and conjunctures in which they are inserted in. In this movement, it was possible to understand how, in the field, the capital, supported by the State, reproduces itself from the non capitalist relations of work, and contradictorily makes possible the rural reproduction that resists the productive restructuration established since the 70 s and intensified in later years with the economic model of agro business. The research revealed that the MPA, originated in the South of Brazil, during the 90 s and in Sergipe in 1999, places itself as a sign of the rural power when it defends and assume the fight for the Feeding Sovereignty project. The conceptions and actions of the MPA in the field in Sergipe and in Brazil, even facing limitations imposed by the capitalism system and by the State, prioritize the struggle against hunger and poverty, understanding that they pass directly under the right of feeding assured in the rural territory. The Feeding Sovereignty proposition is an alternative of rupture from the neoliberal agricultural policies imposed by the Business World Organization (OMC), World Bank (BM) and the International Monetary Fund (FMI), to make possible other form of rural production in a project that assures food for the population. With the Feeding Sovereignty, all a conjuncture is combined: local production, agro toxic free food, price equality, food access, poverty reduction, land reform. In the end, the restitution of the natural resources control (such as land, water and seeds) to the communities, against the life privatization imposed by the logic of capital.